2015
DOI: 10.1353/ajm.2015.0013
|View full text |Cite
|
Sign up to set email alerts
|

On the boundedness of the bilinear Hilbert transform along “non-flat” smooth curves

Abstract: We are proving L 2 (R) × L 2 (R) → L 1 (R) bounds for the bilinear Hilbert transform HΓ along curves Γ = (t, −γ(t)) with γ being a smooth "non-flat" curve near zero and infinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…In his proof, he combined results and tools from both time-frequency analysis and oscillatory integral theory and used ingeniously a uniformity concept (the so-called σ-uniformity; see [11,Section 6]). Lie [13] improved Li's results both qualitatively, by extending monomials to more general curves (certain "slow-varying" curves with extra curvature assumptions), and quantitatively, by improving the estimates. Instead of using Li's method of σ-uniformity, Lie used a Gabor frame decomposition to discretize certain operators in a smart way and then worked with the discretized operators which have variables separated on the frequency side and preserve certain main characteristics (see the appendix of [13] for a detailed comparison between their methods).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In his proof, he combined results and tools from both time-frequency analysis and oscillatory integral theory and used ingeniously a uniformity concept (the so-called σ-uniformity; see [11,Section 6]). Lie [13] improved Li's results both qualitatively, by extending monomials to more general curves (certain "slow-varying" curves with extra curvature assumptions), and quantitatively, by improving the estimates. Instead of using Li's method of σ-uniformity, Lie used a Gabor frame decomposition to discretize certain operators in a smart way and then worked with the discretized operators which have variables separated on the frequency side and preserve certain main characteristics (see the appendix of [13] for a detailed comparison between their methods).…”
Section: Introductionmentioning
confidence: 89%
“…We use the methods that are used in Li [11] (with modifications). Although we use different methods from Lie [13], the curves we consider are similar and the estimates we get are the same.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If P (t) = 2t, this is the classical bilinear Hilbert transform, which is the subject of Lacey and Thiele's breakthrough papers [LT97], [LT98] and has since been studied extensively. For certain nonlinear P the operator in (1.2) has recently been studied in [Li13], [Lie11], [LX16], [GX16], [Lie15]. We invite the reader to consult these papers to learn about the development of this subject.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when P and Q are distinct linear polynomials, B P,Q is in fact the famous bilinear Hilbert transform, whose boundedness was proved by Lacey and Thiele in a pair of breakthrough papers ( [11,12]). Xiaochun Li [15] first studied the case P (t) = t, Q(t) = t d , d ∈ N, and showed that B P,Q is bounded from L 2 × L 2 to L 1 (see also [9,16] for some generalizations). Together with Lechao Xiao, Li later ( [17]) obtained the L p estimates in full range when P (t) = t and Q is any polynomial without linear term.…”
Section: Introductionmentioning
confidence: 99%